scSNPdemux: a sensitive demultiplexing pipeline using single nucleotide polymorphisms for improved pooled single-cell RNA sequencing analysis - Wong, John K. L.; Jassowicz, Lena; Herold-Mende, Christel; Seiffert, Martina; Mallm, Jan-Philipp; Lichter, Peter; Zapatka, Marc (BMC bioinformatics, 2023)
Here we present scSNPdemux, a sample demultiplexing pipeline for single-cell RNA sequencing data using natural genetic variations in humans. The pipeline requires alignment files from Cell Ranger (10× Genomics), a population SNP database and genotyped single nucleotide polymorphisms (SNPs) per sample. The tool works on sparse genotyping data in VCF format for sample identification.
Gesehen am 31.10.2023